Music as atmosphere. Lines of becoming in congregational worship (Lebenswelt. Aesthetics and philosophy of experience., 2015)
In this paper I offer critical attention to the notion of atmosphere in relation to music. By exploring the concept through the case study of the Closed Brethren worship services, I argue that atmosphere may provide analytical tools to explore the ineffable in ecclesial practices. Music, just as atmosphere, commonly occupies a realm of ineffability and undermines notions such as inside and outside, subject and object. For this reason I present music as a means of knowing the atmosphere. The first part of this paper points to the limits of an understanding of atmosphere as a constellation of things, as proposed by Gernot Böhme. In contrast to this, Hermann Schmitz conceptualises atmosphere as half-thing which suggests movement. Drawing on this, I propose to methodologically approach atmospheres as movements. Consequently, in the second part of this paper I closely analyse two motions as they cohere in Closed Brethren worship services: first, becoming (Deleuze and Guattari), a movement on the level of the individual worshiper; secondly, territorialisation (Deleuze and Guattari), a movement of the atmosphere towards its solidification. Here music as atmosphere is not a system of moral signification but a generative power affording intimate processes of divine encounter, whilst producing affective denominational difference.